Effect and safety of treatment with ACE-inhibitor Enalapril and β-blocker metoprolol on the onset of left ventricular dysfunction in Duchenne muscular dystrophy: a randomized, double-blind, placebo-controlled trial - Dittrich, Sven; Pattathu, Joseph George; Ebinger, Friedrich; Eichhorn, Joachim; Motz, Reinald; Korenke, Christoph; Freund, Matthias; Schumacher, Michael (Orphanet journal of rare diseases, 2019)
X-linked Duchenne muscular dystrophy (DMD), the most frequent human hereditary skeletal muscle myopathy, inevitably leads to progressive dilated cardiomyopathy. We assessed the effect and safety of a combined treatment with the ACE-inhibitor enalapril and the β-blocker metoprolol in a German cohort of infantile and juvenile DMD patients with preserved left ventricular function.